تطبيق طريقة الأسرار المتسلسلة لترقية مهارة الاستماع في الفصل العاشر بالمدرسة العالية الإسلامية هاشم أشعري جوغوروطو جومبانج - Isna Wulidatul Auliya; Fathur Rohman (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2025)
This study aims to describe the application of the chain whisper method in Arabic language learning at MA Hasyim Asy'ari Jogoroto Jombang, examine its contribution to improving listening skills (maharah istima'), and identify factors that support and hinder its implementation. This research uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing, and data validity testing using triangulation techniques. The results showed that the chain whisper method-which is done by delivering Arabic sentences in chains from one student to another-can foster enthusiasm for learning, increase accuracy in distinguishing Arabic phoneme sounds, and help students recognize letter makhraj more precisely. This is reflected in the improvement of student learning outcomes. Supporting factors for the implementation of this method include the active involvement of students and the spirit of cooperation in groups, while the main obstacle is the difference in students' educational backgrounds, especially for those who come from public schools who are not familiar with Arabic. This method shows potential as an alternative learning strategy to develop listening skills in a madrasah environment.